To determine therapeutic effect of curcuma gel on gingivitis as an adjunct to scaling: A randomized control trial - M V Devarathnamma; Anunay Bhaskarrao Pangarikar; Prachi Gurunath Parab; Shivanand Aspalli; Nagappa Guttiganur; Janavathi Rangappa (Wolters Kluwer Medknow Publications, 2023)
Context: Gingivitis is among the most prevalent periodontal disease occurring in the oral cavity, which is plaque induced and if untreated, can progress to periodontitis. Various adjunct chemotherapeutic agents are available for plaque control with their own pros and cons. Hence, a plaque-controlling therapeutic agent which is readily available at low cost and without any side effects is the need of the hour. According to the ancient texts, Ayurveda and the traditional culture of India, Curcuma longa is used externally for inflammation of skin and mucosa. Aims: To evaluate the therapeutic effect of curcuma gel on gingival health and its possible usage in the treatment of gingivitis. Settings and Design: This study comprises hundred participants with gingivitis which were divided randomly in two groups. Subjects and Methods: Experimental group - Scaling and topical application of curcuma gel and control group - Scaling alone without the topical application of curcuma gel. Clinical parameters (Gingival Index, Gingival Bleeding Index, and Plaque Index) were assessed at different time intervals (0, 7, 14, and 21 days) in both experimental and control groups. Statistical Analysis Used: Within groups, a repeated measures ANOVA model was used for repeated observations over a period which is followed by the Dunnett test for multiple comparisons. Experimental and control groups were compared for normally distributed data by Student's t-test. Whereas for skewed data, the Wilcoxon test or Mann-Whitney U-test was employed. Results: Statistically significant improvement of gingival health parameters was seen in the group which received topical curcuma oral gel application after scaling compared with the control group. Conclusions: Significant improvement in clinical parameters of gingivitis on the application of Curcuma oral gel after scaling with no obvious adverse effects suggesting its possible use as a topical adjunct treatment in clinical or community level prevention as well as treatment programs in the future.